Exploring the Ethical Dimensions of Testing and Assessment: An Investigation Into Grade Inflation Among EFL Teachers - Wibowo, Enggar Pangesti; Lestari, Ayu; Adrian, Merry; Firdausiyah, Kanaya Salsabila; Islamiy, Jiaul Haque; Putri, Raudhah Diara; Kemal, Taufiq; Kurniawan, Eri (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
Concerns over grade inflation have been raised since teachers tend to give students higher grades than they should. If the level of achievement does not correspond to an appropriate improvement in quality, it can raise concerns about the value of grades as a meaningful measure of academic achievement as well as the integrity and effectiveness of the education system. This research aims to find out how EFL teachers perceive grade inflation and what procedures and ethical considerations they follow in the grade inflation process. A descriptive qualitative study was employed using structured questionnaires and semi-structured interviews with two high school EFL teachers in Bandung. The result showed that although academic performance remains a central consideration, unconscious biases may influence grading when student behavior is factored into assessments. Moreover, teachers acknowledge the dilemma of doing grade inflation where they actually get pressure implicitly from the assessment system, which often takes the form of minimum competency standard (KKM/KKTP). However, they approach it positively, viewing it as an opportunity to enhance student abilities. Despite employing different procedures and assessment criteria in their grade inflation practices, both teachers incorporate ethics. This highlights the need for all teachers to understand and implement ethical grading practices.